ICT Adoption Readiness and ICT Policy Implementation in Secondary Schools in Mayuge District, Uganda - Mukhula, Gideon James; Manyiraho, Deborah; Zami Atibuni, Dennis; Kani Olema, David (American Journal of Educational Research, 2021)
This study explored the levels of and relationship between ICT adoption readiness and ICT policy implementation in Secondary Schools in Mayuge District. The objectives included determining the level of ICT adoption readiness, establishing the level of ICT policy implementation and examining the relationship between ICT adoption readiness and ICT policy implementation. A cross-sectional survey research design employing both quantitative and qualitative approaches was used. A sample of 232 teachers was selected from both private and public secondary schools using simple random sampling technique to participate in the study. Three District Inspectors of Schools (DIS) selected purposively also participated in the study. A questionnaire containing closed ended questions was used to collect quantitative data from the teachers, while an interview guide was used to obtain qualitative responses from the DIS. The quantitative data were analyzed using descriptive statistics: frequencies, percentages, means and standard deviations, while the qualitative data were analyzed using thematic content analysis. The results revealed a moderate overall level of ICT adoption readiness (M = 42.19, SD = 10.10), a moderate overall level of ICT policy implementation (M = 85.11, SD = 9.88), and a significant moderate positive relationship (r = .50, p < .01) between ICT adoption readiness and ICT policy implementation. From the results it was concluded that secondary schools in Mayuge District were in the early stages of domestication of ICT and ICT policy implementation. It was recommended that concerted effort be directed towards improving schools’ ICT adoption readiness in order to improve ICT policy implementation.
Keywords: Information; Communication; Technology; Adoption; Readiness; Policy; Implementation